Preliminary Validity of a Wireless Lighting System (WLS) for Cognitive–Motor Response Assessment, and Its Relationship with Motor Function and Activities of Daily Living in Patients with Stroke. - Kim, Yun-Ho; Lee, Nam-Gi; Seo, Seul-Gi (NeuroRehabilitation, 2026)
Background: As interest in dual-task rehabilitation for stroke patients, which integrates cognitive and motor functions, continues to grow, there is increasing recognition of the need to expand cognitive assessments to include motor components. Objective: This study aimed to evaluate the preliminary evidence for the validity of the Wireless Lighting System (WLS) as a sensor-based cognitive–motor response assessment tool in stroke patients and to investigate its relationship with motor function and activities of daily living (ADL). Methods: Sixty-four patients with stroke were recruited from 'G' rehabilitation hospital. Cognitive function was evaluated using the Korean version of the Mini-Mental State Examination (MMSE-K). Motor function and ADL were assessed using a digital handheld dynamometer, the Berg balance scale, the 10-meter walk test, and the Korean version of the modified Barthel Index, respectively. Cognitive–motor response times were measured using a WLS (Witty SEM). Results: All WLS cognitive–motor response times were moderately negatively correlated with the MMSE-K total score (r = −0.431 to −0.469). Grip strength was only negatively related to the reaction time task (r = −0.363). However, moderate correlations with all WLS tasks were observed for balance (r = −0.512 to −0.602), gait (r = 0.399 to 0.513), and ADL (r = −0.563 to −0.650). Conclusion: These findings provide preliminary evidence supporting the potential utility of the WLS as a sensor-based cognitive–motor response assessment tool in identifying combined cognitive and motor impairments. However, given this study's cross-sectional design and single-center setting, further longitudinal and validation studies are required to establish clinical applicability.